Some approximation properties of the generalized Baskakov operators. Issue 3 (3rd April 2018) - Patel, Prashantkumar; Mishra, Vishnu Narayan; Örkcü, Mediha
Abstract: The present paper deals with a generalization of the Baskakov operators. Some direct theorems, asymptotic formula and A -statistical convergence are established. Our results are based on a ρ function. These results include the preservation properties of the classical Baskakov operators.